Pulmonary Embolism - A Case Report - Nahar, Samsun; Momenuzzaman, -; Begum, Fatema; Khan, KN; Anisuzzaman, Quazi; Dhar, Razib (University Heart Journal, 2017)
PE remains a clinically challenging diagnosis, more often missed than found, with no decline in its incidental discovery at autopsy over the past 30 years. Pulmonary embolism should be considered in the differential diagnosis of every dyspnoea event that presents at an emergency department. We describe a case of 68 years old man with symptoms of dyspnoea who later diagnosed as pulmonary embolism. This case report emphasizes early diagnosis and treatment to avoid fatal outcome. University Heart Journal Vol. 12, No. 1, January 2016; 40-44